Waves Propagation at an Interface of Two Liquid Saturated Porous Solid Half Spaces - et. al., Anup Singh , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This manuscript is concerned with reflected and refracted elastic waves when transverse waves are incident at the interface between two fluid-saturated porous solid half-spaces. Perfect and imperfect both types of contact of the interfaces are discussed. It has observed that for a specific model the behaviour of different reflected, refracted waves and the ratio of their amplitudes depend on the physical properties of the medium, angle of emergence, the porosity of the fluid, the porosity of fluid drenched incompressible porous medium and stiffness of imperfect boundary. The computer numerically results for this model have been presented graphically by taking a particular case of empty porous solid.